PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN CAFE TOO EZ FOR COFFEE BALIKPAPAN - Sukimin Sukimin; Nurlia Nurlia; Devi Sriwulan (Jurnal GeoEkonomi, 2024)
The purpose of this study is to determine whether the product, price, place, promotion, people, process, and physical evidence simultaneously affect the purchasing decisions of consumers of Cafe Too Ez For Coffee Balikpapan. And to find out whether the product, price, place, promotion, people, process, and physical evidence partially affect the purchasing decisions of consumers of Cafe Too Ez For Coffee Balikpapan. The number of samples in this study was 268 Consumers of Cafe Too Ez For Coffee Balikpapan. The sampling technique used in this study is Non Probability Sampling and the sample method used is Accidental Sampling. The data analysis model used in this study is Multiple Linear Regression. The test equipment used is Instrument Test, Classical Assumption Test, and Hypothesis Testing. The results show that the hypothesis proposed in this study can be accepted as true, namely, it is suspected that the product, price, location, and promotion partially affect the purchasing decisions of consumers at Cafe Too Ez For Coffee Balikpapan, as evidenced by the t-count value is greater than the t-table value. And product, price, location, and promotion simultaneously affect the purchasing decisions of consumers of Cafe Too Ez For Coffee Balikpapan, it is proven because the calculated F value is greater than the F table value.